Characterizing Strategy Use During the Performance of Hippocampal-Dependent Tasks - Clark, Ian A.; Monk, Anna M.; Maguire, Eleanor A. (Frontiers in Psychology, 2020)
Recalling the past, thinking about the future and navigating in the world are linked with a brain structure called the hippocampus. Precisely how the hippocampus enables these critical cognitive functions is still debated. The strategies people use to perform tasks associated with these functions have been under-studied, and yet such information could augment our understanding of the associated cognitive processes and neural substrates. Here, we devised and deployed an in-depth protocol to examine the explicit strategies used by 217 participants to perform four naturalistic tasks widely acknowledged to be hippocampal-dependent, namely, those assessing scene imagination, autobiographical memory recall, future thinking and spatial navigation. In addition, we also investigated strategy use for three laboratory-based memory tasks, one of which is held to be hippocampal-dependent – concrete verbal paired associates – and two tasks which are likely hippocampal-independent – abstract verbal paired associates and the dead or alive semantic memory test. We found that scene visual imagery was the dominant strategy not only when mentally imagining scenes, but also during autobiographical memory recall, when thinking about the future and during navigation. Moreover, scene visual imagery strategies were used most frequently during the concrete verbal paired associates task, whereas verbal strategies were most prevalent for the abstract verbal paired associates task and the dead or alive semantic memory task. The ubiquity of specifically scene visual imagery use across a range of tasks may attest to its, perhaps underappreciated, importance in facilitating cognition, whilst also aligning with perspectives that emphasise a key role for the hippocampus in constructing scene imagery.